(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article discusses the importance of online learning technologies, teacher-student relationships, and methods for determining mastery in distance learning. In addition, the current state and problems of distance learning and teaching, as well as the conceptual framework for creating distance courses, are reviewed.